Conclusion: policy diversity in Germany's federalism - Schmidt, Manfred G. (German politics, 2016)
This article will examine the extent to which the narrative of policy diversity is characteristic of German federalism, using findings from comparisons of policies in the individual Länder and with a special focus on the period since the German reunification.
Gesehen am 19.05.2020